Reconceptualizing Parental Awareness in Early Childhood Learning: A Qualitative Exploration of Interpretive Processes and Socio-Pedagogical Dynamics - Regita Riani Putri; Saharudin Saharudin; Syahrial Syahrial; Urip Sulistiyo; Benoudjafer Ibtissam (Jurnal Pendidikan Anak, 2026)
Purpose: This study addresses a critical theoretical gap in early childhood education by reconceptualizing parental awareness not as a static set of observable practices, but as a dynamic, interpretive process. Methodology: Employing a qualitative single-case study design, this research involved semi-structured interviews with six parents of early childhood learners. Data analysis was conducted using inductive thematic analysis supported by NVivo to explore the subjective processes through which parents make meaning of their children’s learning experiences. Findings: The findings reveal that parental awareness is a context-dependent, socially constructed process shaped by continuous interactions across home, school, and social environments. Four interrelated dimensions emerged: (1) awareness in school transition, (2) awareness of children’s learning patterns in daily activities, (3) awareness in educational decision-making within social contexts, and (4) awareness shaped through school communication. These results demonstrate that parents actively interpret, negotiate, and reconstruct their understanding of children’s learning rather than merely implementing predefined pedagogical practices. Implications: This research extends existing bio-psycho-social-digital frameworks by shifting the focus from measurable involvement to the internal, reflective processes that underpin meaningful parental engagement. Recommendations: Future pedagogical and institutional efforts should prioritize strengthening collaborative communication frameworks that support parents in their role as reflective agents, thereby ensuring more holistic and resilient learning ecosystems. Originality/Value: Grounded in the necessity of socio-pedagogical integration, this research provides empirical insight into the subjective dimensions of parental awareness, offering a more holistic lens for understanding parent–child–school interactions in contemporary early childhood settings.